EXAMINING TRANSLATION TECHNIQUES IN ENGLISH AND CHINESE CINEMA TITLES: AN IN-DEPTH ANALYSIS - Chen , Jie; Fang, Liu (Research Journal of Literature, Languages and Linguistics, 2024)
Film titles serve as an important tool for film promotion and attract the attention of the audience. The translation of film titles is crucial when films are viewed globally. This article is a contrastive study of English and Chinese film titles and focuses on the language characteristics of film titles and the different translation methods used for realizing the film's functions. The four main functions of film titles are informative, expressive, vocative, and aesthetic, each playing a significant role in the promotion of the film. The study highlights the similarities and differences between the two languages in terms of word structure, thinking, and cultural backgrounds. The article emphasizes the necessity of appropriate translation methods that retain the original charm and conform to the characteristics of the target language to spread culture and promote the film better. This work suggests that a literal translation can be preferred when foreign audiences can understand the meaning of the original titles. Still, free translation may be used to better convey the general idea of the original text when the title’s meaning loses its significance in translation. The study points out some of the existing problems in Chinese film title translations that can mar the effective promotion of films. This article provides insights into film title translation and contributes to the development of film title studies.